A Estrutura e a prática organizacional da Secretaria de Estado de Administração e Gestão do Amazonas - Pinheiro, Hellen Cremildes Porto Santana (2008)
The contemporany state is confronted with new offers and demands from society, involved in crisis and contradictions that bring forth the search for new management alternatives; either because The Social state model is marching towards a new paradigm; or because it is going through tough, critical moments of management, fiscal exhaustion or bureaucratic disfunctions. Whichever case, the state is under transformation, and fast, aligning itself to a complex and turbulent environment of modern management, where players who act, in general, influencing the way labor is done, therefore, interfering in the structural model of public government agencies. The present research work aims at analysing the Management and Administration State Government Agency of Amazon (SEAD), covering its contextual dimensions, verifying whether organizational practices are compliant with its structure. The literature aid will try to clarify important questions for the evolution of this present work, such as: wich is SEAD`s structure and which practices are observed? Such keyquestions will provide the foundation for the answer to the main question which is: Is the Management and Administration State Government Agency of Amazon (SEAD) organizational practice compliant with its structure?